Renewable energy consumption, carbon emissions and oil prices: a panel data analysis for G7 and BRICT countries - Bashirov, Gulmammad. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Economic and social concern on energy dependence and climate change is making renewable energy the central theme of decision-making in energy policies and consumption. This thesis brings forward and builds an empirical model of renewable energy consumption in G7 and BRICT countries over the period 1990-2013. Results of our analysis show that both in G7 and BRICT countries, increases in oil prices have positive effect on renewable energy consumption. However, GDP per capita and renewable consumption are negatively related in G7 countries, but positively related in BRICT countries. For BRICT countries, on the other hand, estimates found no significant relationship between carbon emissions and renewable consumption, yet a positive relation is observed for G7 countries. As the estimates differ across countries, it might be helpful to account domestic factors.
Keywords: Renewable energy sources.; Energy conversion.